Soil Systems for Upscaling Saturated Hydraulic Conductivity for Hydrological Modeling in the Critical Zone - Libohova, Z. (2020)
The objectives of this research were (i) to assess the ability of Amoozemeters, wells, piezometers, and flumes to accurately represent Ksat at a small catchment scale and (ii) to extrapolate Ksat to a larger watershed based on available soil data and soil landscape models for simulating streamflow using the Distributed Hydrological Soil Vegetation Model. The mean Ksat between Amoozemeters, wells, and flumes varied from 2.4 to 4.9 × 10−7 m s−1, and differences were not significant. Mixed trends in mean Ksat for slope positions and soil series were observed. The strongest significant and consistent trend in mean Ksat was observed for soil depth. The mean Ksat decreased exponentially with depth, from 6.51 × 106 m s−1 for upper horizons to 2.37 × 10−7 m s−1 for bottom horizons. Recognizing the significantly decreasing trend of Ksat with soil depth and the lack of consistent trends between soils and slope positions for small catchments, Ksat values were extrapolated from the small catchments occurring in Dillon Creek to another large watershed (Hall Creek) based on soil similarity and distribution. The Nash–Sutcliffe model overall efficiency of 0.52 indicated a good performance in simulating streamflows without model calibration. Combining Ksat measurement methods in small catchments with an understanding of soil landscapes and soil distribution relationships allowed successful upscaling of localized soil hydraulic properties for streamflow predictions to larger watersheds.